Human rights perspectives on climate change adaptation: Civil society experiences in Cambodia and Kenya - Ian Christoplos; Mikkel Funder; Colleen McGinn; Winnie Wairimu (Danish Institute for International Studies (DIIS), 2014)
A growing number of civil society organisations apply human rights based approaches in their work. But what are the practical experiences with such approaches in climate change adaptation? This new DIIS report examines how NGOs in Cambodia and Kenya are approaching the issue of human rights in their efforts to support climate change adaptation. The report finds that while some NGOs are engaging human rights issues in climate change directly and openly through a "hard advocacy" approach, most choose a different strategy: In a political context where human rights remain highly sensitive, some NGOs avoid the issue of rights altogether, and focus instead on the technical aspects of climate change adaptation. Others apply a "soft advocacy" approach in which they seek to influence rights issues indirectly by collaborating with government agencies. The report discusses the nature and impact of these different approaches to human rights in climate change, and the perceptions and challenges that they reflect.
Keywords: 300; Climate change and environmentInequality and poverty; Land rights and investments; Oil; gas and minerals; Cambodia; Kenya; Asia